Perencanaan dan Pengorganisasian Program Bimbingan dan Konseling - Ali Daud (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2016)
Planning and Organizing guidance and counseling programs in schools involving people inside the organization Guidance and Counselling in schools and the division of labor among member organizations in school guidance. In order that all guidance and counseling services running properly. Administration covers administrative guidance and counseling to people (personnel guidance) and administration of the activities performed by the person. Mechanism of action of each Teacher of Guidance and Counseling in gathering information, data, or facts, pathways administrative mechanism different path, but still converge the specific purpose of solving the problems faced by students.